Osteopontin-Enriched Algae Modulates the Gut Microbiota Composition in Weaning Piglets Infected with Enterotoxigenic Escherichia Coli (P06-069-19). (13th June 2019) - Wang, Mei; Smith, Brooke; Adams, Brock; Tran, Miller; Dilger, Ryan; Donovan, Sharon
Abstract: Objectives: Enterotoxigenic Escherichia coli (ETEC) are an important cause of diarrhea in human infants and young farm animals. Osteopontin (OPN), a glycoprotein present in high concentration in human milk, has immunomodulatory functions, which could indirectly impact the microbiota. Furthermore, a previous study has shown fecal microbiota composition differs between wild-type and OPN knockout mice. Herein, the effects of OPN-enriched algae on the gut microbiota composition and volatile fatty acid (VFA) concentrations of ETEC-infected piglets were assessed. Methods: Naturally-farrowed piglets were sow-reared for 21 days and then randomized to two weaning diets: WT (formula + 1% wild-type algae) or OPN (formula + 1% OPN-enriched algae). On postnatal day (PND) 31, all piglets were infected orally with a live culture of ETEC (10 10 colony-forming unit/3 mL dose) daily for three consecutive days. On PND 41, ascending colon (AC) contents were collected. Gut microbiota was assessed by sequencing V3-V4 regions of 16S rRNA gene and VFAs were determined by gas chromatography. Alpha-diversity and VFAs were analyzed using PROC MIXED procedure of SAS. Beta-diversity was evaluated by permutational multivariate analysis of variance (PERMANOVA) and differential abundance analysis on the bacterial genera was performed using DESeq2 package of R. Results: Shannon indices were lower in the AC contents of OPN piglets compared to WT piglets. The overall colonic microbiota of OPN piglets differed from that of WT piglets (PERMANOVA P  = 0.015). At genus level, OPN-enriched algae increased the abundance of Streptococcus, decreased the abundances of Sutterella, Candidatus Soleaferrea, dga-11 gut group, Rikenellaceae RC9 gut group, Ruminococcaceae UCG-010, uncultured Ruminococcaceae, Prevotella 2 and 7 compared to piglets consuming wild-type algae ( P  < 0. 05). OPN piglets also had higher ( P  <   0.05) concentrations of acetate, propionate, butyrate and valerate compared to WT. Conclusions: In ETEC infected piglets, 1% OPN-enriched algae decreased alpha-diversity and modulated the microbiota composition and VFA profiles compared to 1% WT algae. Other studies have shown that OPN inhibits biofilm formation in vitro, but future research is needed to assess in vivo microbiome-modulation mechanisms. Funding Sources: Triton Algae Innovations.